Juana and the sacred shores Aisha Polestico's journey before, during, and after creating a dance film as a recital under the UP College of Music Dance Program - Polestico, Aisha Josephine L.; Medina, Desiree (Diliman, Quezon City U.P. College of Music, 2019)
"This thesis entitled Juana and the Sacred Shores: Aisha Polestico's JOurney Before, During, and After Creating a Dance Film as a Recital Under the UP College of Music Dance Program is a study about the dance film medium and a documentation of the first dance film made as a recital under the UPCMu dance program. Juana and the Sacred Shores is a result of a collaboration between the recitalist, Aisha Josephine Polestico (dancer and choreographer) and Antonne Rafael Santiago, a film major in the UP College of Mass Communication. The output of their work is the main medium in Polestico's recital and the thesis film of Santiago, a major requirement in his course as well. This study focuses on analyzing the process behind Juana and the Sacred Shores, assessing its effectiveness as a dance film, and deals with concepts and theories about the dance film medium related to the analysis of the film.
Thesis (B.M. Dance) -- University of the Philippines, Diliman.
Includes bibliographical references and appendices.
Keywords: Dance; Choreography